China-Indonesia People-to-people exchanges in the New Era: Mechanisms, Current Situation and Challenges - Wei, Xinyue; Sun, Chen; Zhao, Zhangfeng (International Journal of Chinese Interdisciplinary Studies, 2024)
People-to-people exchanges are the public opinion basis for China and Indonesia to carry out cooperation in various fields, and are also an important cornerstone for the two countries to build a community with a shared future. Bilateral and multilateral high-level dialogue mechanisms provide an effective platform for people-to-people exchanges. The overall improvement of China-Indonesia relations, deepening of political mutual trust and close economic cooperation have laid a realistic foundation for bilateral people-to-people exchanges. In the new era, cooperation of bilateral people-to-people exchanges have achieved fruitful results, mainly in education, science and technology, sports, youth, tourism and digital fields. At present, the China-Indonesia people-to-people exchanges’ mechanism continues to develop and the areas of cooperation continue to expand, forming a pattern of multi-level exchanges between GO and NGO. At the same time, the deepening of people-to-people exchanges still faces challenges such as Indonesia’s internal factors, insufficient people’s exchanges, and the Indo-Pacific geopolitical structure.